Penerapan Kegiatan Melipat Kertas Origami untuk Mengembangkan Keterampilan Motorik Halus Anak Di Kelas B Ra Al-Hidayah - Vera Siti Magfiroh; Vera Yuliani; Uswatur Rohmah; Uswatun Hasanah; Vera Oktafia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to develop children's fine motor skills through origami paper folding activities in class B RA Al-Hidayah. Fine motor skills are very important for early childhood because they affect their ability to do activities that require hand and finger coordination, such as writing, cutting, and drawing. Origami paper folding activities were chosen because they involve structured hand movements and train children's accuracy, patience, and creativity. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of the study were 20 children in class B RA Al-Hidayah. Data were collected through observation, field notes, and documentation of children's work, then analyzed descriptively qualitatively and quantitatively. The results showed that children's fine motor skills increased significantly after the implementation of origami folding activities. In cycle I, the percentage of children who achieved good category fine motor skills was 65%, and increased to 90% in cycle II. Children looked more skilled at controlling finger movements, folding neatly, and enthusiastically participating in activities. Thus, the implementation of origami paper folding activities is effective in developing children's fine motor skills in RA Al-Hidayah. This activity can be used as an alternative learning that is fun and beneficial for the development of early childhood.